Penetapan Metode Anuitas pada Pembiayaan Murabahah Bank Aceh Syariah Perspektif Asas Keadilan - Putri, Raihan; Mujib, Abdul; Eriyanti, Nahara (Sharia Faculty Islamic Economic Law Study Department, 2023)
One of the methods used to calculate margins on murabahah financing is using an annuity calculation system. There is a problem of taking large profits at the beginning of payment causing customers to complain, setting annuity margins is considered not to provide justice for customers. In this case the author wants to examine and analyze the determination of the annuity method in the financing of Bank Aceh Syariah in terms of the principle of justice. In this research, the type of research used is library research. Based on this research, it was concluded that the determination of the annuity method used by Bank Aceh Syariah in the category of fulfilling the principle of justice for the customer is injured because the application of the annuity method at Bank Aceh Syariah contains a pattern of principal installment payments that changes to be higher and determination of profits whose value changes to be small. In the concept of Islamic justice or contained in Law Number 21 of 2008 regarding the concept of justice explains that transactions between customers and banks must obtain a form of justice. In practice the application of the annuity method tends to be manipulative so that the disbursement procedure seems burdensome to the customer. The application of the customer annuity method will incur a loss when the customer wants to pay off at the beginning but does not get an installment discount. The sense of injustice in an annuity can be eliminated and then realized, namely by making a deduction on the installments for each customer who pays off obligations at the beginning of the transaction.